Posyandu Sebagai Sentra Pendidikan Masyarakat Bagi Anak Usia Dini - Azmi Islami; Supriati H. Rahayu; Yayah Rukhiyah; Wulan Fauzia; Umayah Umayah; Tatu Dinar Rahmalia (UIN Sultan Maulana Hasanuddin Banten, 2023)
The aim of the study was to identify the motivations for involvement of members of the Parumasaan rural community in Serang District in visiting Posyandu. Such studies are useful in broadening the horizons of early childhood development in rural areas in addition to disseminating the benefits for community-based early childhood education through Posyandu. Qualitative research methods are the main instrument with observation, interviews and documentation. The interviews were mainly addressed to the visitors from women. The results of the activities show that there are many Posyandu activities and programs that have an impact on the knowledge of visitors in caring for early childhood, whether received directly from the organizers or discussions with fellow mothers. Such knowledge can change people's mindset about nutrition and child development from an early age